Numerical simulation of III-V solar cells using D-AMPS - Barrera, Marcela Patricia; Rubinelli, F.; Plá, Juan Carlos; Rey-Stolle, I. (25th European Photovoltaic Solar Energy Conference and Exhibition / 5th World Conference on Photovoltaic Energy Conversion, 2010)
Fil: Barrera, Marcela Patricia. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina